THE INFLUENCE OF THE ACIDIC TREATMENT OF PEAT ON ITS SORPTION PROPERTIES (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
The influence of the acidic treatment of peat on its sorption properties has been studied by means of optical emission spectrometry with inductively coupled plasma (ICP-OES) and pH-metry methods. Untreated peat of the Vardenis deposit, Armenia, and acid-activated peat were used as sorption materials. As an activation process, we consider preferably the elimination of metal ions captured on the peat surface. During this active sorption groups (particularly acetic) are released from the surface and such acidic groups together with other functional groups begin to act according to the cation exchange mechanism.
Keywords: adsorption; heavy metals; peat-based sorbents